Enhancing long-term adherence in elderly stroke rehabilitation through a digital health approach based on multimodal feedback and personalized intervention - Xintong Wen; Yuxuan Li; Qi Zhang; Zhiwei Yao; Xijie Gao; Zhibo Sun; Xing Fang; Wei Huang (Scientific Reports)
Abstract Multimodal digital health technologies aim to improve long-term adherence in stroke patients through personalized feedback and psychological monitoring. However, the interactive effects of physiological and psychological factors on rehabilitation adherence remain unclear. This study evaluates personalized feedback, physiological and psychological factors, and their independent and synergistic effects to optimize rehabilitation adherence in elderly stroke patients. This study was designed as a longitudinal study, with data collected from 180 participants across two central hospitals between March and September 2024. A linear mixed effects model (LMM) was used to analyze the impact of physiological monitoring, psychological monitoring, and personalized feedback mechanisms on long-term patient adherence. Data were gathered through structured questionnaires, resulting in a final sample size of 540 data points. The time effect has a significant positive effect on rehabilitation compliance. The rehabilitation plan completion rate (A1) increases by 1.25 (t = 34.25) and 2.28 units (t = 62.56) in the mid-term follow-up (T2) and long-term follow-up (T3) respectively; the self-reported compliance score (A2) increases by 1.12 (t = 31.39) and 2.3 points (t = 64.27) at T2 and T3 respectively; the completion of specific activities (A3) increases by 1.37 (t = 50.34) and 2.34 units (t = 86.26); the number of interruptions (A4) decreases by 0.89 (t = -17.31) and 2.11 times (t = -41.17) respectively. In personalized feedback, high-quality feedback (D2) significantly promotes compliance (β = 0.0318, t = 2.08), while excessively frequent feedback (D1) showes a negative impact (β=-0.0914, t=-1.93 ). In terms of psychological factors, positive emotion (C3) has a significant positive effect on compliance (β = 0.1572, t = 2.695), while depressed emotion (C1) significantly reduces interruption behavior (β=-0.0885). The interaction effect between physiological factors and psychological factors is not significant, indicating that their influence is relatively independent. This study demonstrates that personalized feedback, psychological support, and time effects are essential for enhancing rehabilitation adherence in elderly stroke patients. High-quality, relevant feedback significantly improves adherence, while ineffective feedback may have adverse effects. Positive emotions within psychological factors promote adherence, whereas depressive emotions hinder recovery, underscoring the importance of psychological support. Although physiological and psychological factors lack significant interactive effects, their independent influences merit attention and optimization in rehabilitation interventions.